TINGKAT MARGIN, INFLASI, DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN TERDAFTAR DI BEI TAHUN 2009-2018 - suhendi sema (UIR Press, 2022)
This research was conducted to determine how the influence of margin rates, inflation, and debt to equity ratio on stock prices of banking companies listed on the Indonesia Stock Exchange. Data taken from www.idx.co.id. The data used was from 2009 to 2018. The research was conducted in 2020. The population in this research were 44 companies with a sample used of 28 companies. This research used quantitative data processed by the Eviews 9 application with panel regression method. The test resulted conclude that the inflation variable and the debt to equity ratio partially did not have a significant effect on stock prices of banking companies, while margin rates had a significant effect on stock prices of banking companies. Simultaneously, margin rates, inflation, and debt to equity ratio had a significant effect on stock prices of banking companies. The contribution of margin rate, inflation, and debt to equity ratio variables to stock prices was 4.1%, while the closeness of the margin rate, inflation and debt to equity ratio variables to stock prices was no close.